2013
DOI: 10.3892/or.2013.2836
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis reveals that MAEL, a component of nuage, interacts with stress granule proteins in cancer cells

Abstract: The Maelstrom (MAEL) gene is a cancer-testis (or cancer-germline) gene, which is predominantly expressed in germline cells under normal conditions, but is aberrantly expressed in a range of human cancer cells. In germline cells, MAEL is found predominantly in the nuage, where it plays an essential role in piRNA biogenesis and piRNA-mediated silencing of transposons. However, the role of MAEL in cancer has not been elucidated. We performed immunoprecipitation and Nano-LC-MS/MS analysis to investigate the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
(40 reference statements)
1
17
0
Order By: Relevance
“…Although Mael protein is barely detectable in most normal somatic tissues except testis, recent reports have shown that the protein is highly expressed in somatic cancer patient tissues and cancer cell lines [1518]. Consistent with these reports, RT-PCR and Western blotting demonstrated Mael overexpression in tumor tissues of HCC patients compared with corresponding adjacent liver tissues (Supplementary Figure S2B).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Although Mael protein is barely detectable in most normal somatic tissues except testis, recent reports have shown that the protein is highly expressed in somatic cancer patient tissues and cancer cell lines [1518]. Consistent with these reports, RT-PCR and Western blotting demonstrated Mael overexpression in tumor tissues of HCC patients compared with corresponding adjacent liver tissues (Supplementary Figure S2B).…”
Section: Resultssupporting
confidence: 79%
“…Mael is overexpressed various cell lines derived from a majority of cancer types including lung, breast, prostate and colon through epigenetic modifications [15] and is overexpressed in epithelial ovarian cancer tissue [16] and promotes hepatocellular carcinoma metastasis [17]. Proteomic analysis reveals that Mael interacts with stress granule proteins in cancer cells [18]. …”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, ILKAP was identified to be a component of the MAEL protein complex [ 22 ]. To confirm the protein interaction between MAEL and ILKAP, we performed co-immunoprecipitation (co-IP).…”
Section: Resultsmentioning
confidence: 99%
“…MAEL is also a cancer testis gene regulated by DNA methylation. It interacts with stress gene in cancer cells and promotes hepatocellular carcinoma metastasis by inducing epithelial-mesenchymal transition 38 . This implies lncRNA AC145110.1 is likely to be a hub of the lncRNA-mRNA regulatory network and may thus be involved in the important process of breast cancer development.…”
Section: Discussionmentioning
confidence: 99%